High-risk mucosal HPV types associated with squamous cell carcinoma on the nose tip in an immunocompetent young man - Camila Fátima Biancardi Gavioli; Cyro Festa Neto; Stephen K Tyring; Lana Luiza da Cruz Silva; Walmar Roncalli Pereira de Oliveira (Sociedade Brasileira de Dermatologia, 2018)
Abstract: The oncogenic role of high-risk HPV in anogenital, head and neck, and cervical cancer is well recognized, but not in skin cancer in the general population. Some authors have demonstrated their appearance mainly on the hands and feet, particularly in the area of the nail bed, which could be due to contamination with HPV types from anogenital regions. Here, we describe a case of genital HPV associated with SCC on the nose tip in an immunocompetent young man, which was confirmed by histopathological findings and in situ hybridization. The importance of this report is to highlight the potential role of HPV in the etiology of skin cancer in an immunocompetent individual.